Pheno-I: a new drone and satellite image analysis software - CGIAR Research Program on Rice (2019)
Pheno i has successfully been used and validated to classify the rice Hoja Blanca virus in collaboration between CIAT and FLAR breeders and also by using this application for precision agriculture in a project funded by the UK Space Agency.